Improving the Training of Frontline Extension Workers in Tanzania: A Pilot Curriculum Reform Initiative with the Ministry of Agriculture Training Institute at Ilonga - Mary T. Rodriguez; Mark Erbaugh; Amon Mattee; Catherine Msuya; Fallys Masambuka; Graham Cochran (Journal of International Agricultural and Extension Education, 2019)
Promoting the transition of smallholder farmers from subsistence to more commercial and market-oriented production is an important goal of the Tanzanian extension system. The Ministry of Agriculture Training Institutes (MATIs) contribute to this goal by providing training to frontline extension workers (FEWs). However, the capacity of the MATI system to produce agricultural extension practitioners with job-ready competencies has declined, leading stakeholders and employers to raise concerns about the quality and training of FEWs. The main purpose of this study was to develop recommendations for curriculum revisions at MATI Ilonga to improve its program of study. This was done using a competency-based approach that incorporated inputs from stakeholders into the curriculum assessment and revision process. A panel of eight local and external experts derived 23 competencies from a review of the MATI curriculum and extension literature. A survey instrument to assess competencies based on perceptions of importance and graduates’ ability was designed and administered to 189 stakeholders from four stakeholder groups. Stakeholder-respondents considered all but two of the 23 competencies to be very high importance. Weighted discrepancy scores indicated that the highest rated areas for curriculum revision were Value Chains, Business skills, Climate Change, Fisheries, and Land Resource Management. All stakeholder groups except graduates, indicated Value Chains and Business Skills as high priorities requiring enhanced training to improve the ability of FEWs. Follow-up stakeholder consultations indicated support for using the competency-based approach, engaging stakeholders in the curriculum review process, and interest in applying the approach with other MATIs in Tanzania.
Keywords: Tanzania; agricultural extension; training; competencies